2018
DOI: 10.3892/ijmm.2018.3583
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA methylation in human peripheral leukocytes identifies potential biomarkers of nonalcoholic fatty liver disease

Abstract: The aim of the present study was to uncover the role of leukocytic DNA methylation in the evaluation of nonalcoholic fatty liver disease (NAFLD). Patients with biopsy-proven NAFLD (n=35) and normal controls (n=30) were recruited from Chinese Han population. Their DNA methylation in peripheral leukocytes was subjected to genome-wide profiling. The association between differential methylation of CpG sites and NAFLD was further investigated on the basis of histopathological classification, bioinformatics, and pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Upregulation of the ACSL4 gene accelerates lipogenesis, whereas downregulation of ACSL4 prevents the accumulation of cellular cholesterol [ 34 ]. Previous study also reported leukocytic hypomethylated ACSL4 an index for borderline/definitive NASH, with odds ratio (OR) at 11.44 and 95% confidence interval (CI) from 1.04 to 125.37 (P=0.046) [ 35 ]. In that study, the NAFLD Activity Score (NAS) scoring system has been used for the stratification of clinical phenotypes of NAFLD.…”
Section: Discussionmentioning
confidence: 98%
“…Upregulation of the ACSL4 gene accelerates lipogenesis, whereas downregulation of ACSL4 prevents the accumulation of cellular cholesterol [ 34 ]. Previous study also reported leukocytic hypomethylated ACSL4 an index for borderline/definitive NASH, with odds ratio (OR) at 11.44 and 95% confidence interval (CI) from 1.04 to 125.37 (P=0.046) [ 35 ]. In that study, the NAFLD Activity Score (NAS) scoring system has been used for the stratification of clinical phenotypes of NAFLD.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with the correlation between ASLC4 mRNA expression and prognosis in LIHC, that is, high expression of ACSL4 leads to worse prognosis. A previous study also found that hypomethylated CpG sites of ACSL4 were associated with an increased risk of non-alcoholic fatty liver disease (NAFLD) ( Zhang et al, 2018 ). These results suggest that hypomethylation of ACSL4 may be one of the epigenetic regulatory mechanisms in many cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Hypomethylation of Acyl-CoA synthetase long chain family member 4 ( ACSL4 ) and carnitinepalmitoyltransferase 1 C ( CPT1C ) were linked to a heightened risk of NAFLD and might serve as biomarkers for NAFLD. Further, leukocytichypomethylated ACSL 4 might be a useful biomarker for pathological traits of NAFLD [ 102 ]. In an exploration by Wu et al., using epigenome wide association studies (EWAS) six differentially methylated CpG sites in ACSL4, CRLS1 , CTP1A, SIGIRR, SSBP1 and ZNF622 were identified which could serve as serum biomarkers to distinguish between those with NASH and simple steatosis [ 103 ].…”
Section: Dna Methylation In Nafldmentioning
confidence: 99%